Hypohydration is evident in elite orienteering athletes during a two-day race: a descriptive study - Kerem, M.; Öztürk, F.; Taskin, H. B.; Dudak, E.; Ceylan, B. (BMC Sports Science, Medicine and Rehabilitation, 2025)
This study aimed to present changes in hydration status of orienteering athletes during a two-day race. Twenty elite male orienteers voluntarily participated in the study during a two-day race. Athletes` hydration status was measured two consecutive race days via urine specific gravity (USG) and fluid consumption was followed. There was a significant main effect of time on USG values (F2.32-20.89=3.70, p = 0.04, n2 = 0.29, ES = Large). USG values increased from the day one morning (1.019 ± 0.008) to post-race on day two (1.026 ± 0.003) (p = 0.04), from 3 h post-race on day one (1.018 ± 0.007) to post-race on day two (1.026 ± 0.003) (p = 0.01) and pre (1.019 ± 0.004) to post-race (1.026 ± 0.003) on day two (p = 0.001). Both races worsened hydration level of the athletes and they could not rehydrate post-race on day two despite fluid intake ad libitum. These findings suggest that orienteering athletes presented hypohydration following consecutive races as suggested by USG values on day two. Therefore, specific rehydration plan could be developed and applied for proper hydration status in these athletes.